Ivan Bunin and Evgeny Spektorsky: Сorrespondence (1928–1933)Bunin and Evgeny Spektorsky: Сorrespondence (1928–1933) - Anton V. Bakuntsev; Sergey N. Morozov (Studia Litterarum)
This publication discloses one of the aspects of a broader subject “Ivan A. Bunin and the Russian emigration in Yugoslavia.” The publication presents the correspondence of I.A. Bunin with the scientist-jurist, professor of the Belgrade and Ljubljana universities, the chairman of the Russian Scientific Institute and the Russian matitsa E.V. Spectorsky. The reasons for starting this correspondence were the following: 1) the decision of the Council of the Russian Scientific Institute to invite Bunin as a lecturer (1928); 2) Bunin’s Nobel Prize in literature (1933). The letter of Spektorsky’s successor as chair of the Russian Scientific Institute, professor Fyodor V. Taranovsky to Bunin may be found in the Attachment. The published letters are stored in the Buninsky collection of the Russian archive in Leeds and in the State Archive of the Russian Federation. The article also uses material from the Archive of Foreign Policy of the Russian Empire at the Russian Foreign Ministry and material from the Archive of the Serbian Academy of Sciences and Arts.